A two dimensional recursive inverse adaptive filtering algorithm - Salman, Mohammad Shukri; Hocanin, Aykut; Kukrer, Osman (My University, 2011)
In this paper, a 2-D form of the recently proposed Recursive Inverse (RI) algorithm is introduced. The filter coefficients can be updated both along the horizontal and vertical directions on a 2-D plane. The proposed approach uses a variable stepsize and avoids the use of the inverse autocorrelation matrix in the coefficient update equation, which leads to an improved and more stable performance. In order to compare with the well-known 2-D RLS adaptive filtering algorithm, it is applied to an image deconvolution problem. Simulation results show that the proposed 2-D algorithm leads to improved performance compared to that of the 2-D RLS algorithm. © 2011 IEEE.
İki boyutlu özyineli ters uyarlanir süzgeç algoritmasi
2011 IEEE 19th Signal Processing and Communications Applications Conference, SIU 2011 --
Keywords: Adaptive filtering algorithms; Autocorrelation matrix; Filter coefficients; Image deconvolution; RLS algorithms; Simulation result; Variable step size; Vertical direction; Adaptive filtering; Adaptive filters; Deconvolution; Signal processing; Adaptive algorithms